ANALISIS INTERAKSI SOSIAL SISWA SERTA KAITANNYA TERHADAP HASIL BELAJAR MATEMATIKA DI SMK N 1 SOSORGADONG - Nunik Ardiana; Muhammad Syahril Harahap; Vijay Andreas Manik (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Abstract This study aims to analyze students' social interactions and their relation to learning outcomes of mathematics at SMK N 1 Sosorgadong. This research approach is descriptive qualitative. The research subjects were 22 students. Observations, interviews and documentation were used in data collection and triangulation techniques were used in technical analysis. The results showed that the average social interaction on students' mathematics learning outcomes was 67.5 in the sufficient category. It was concluded that the social interactions of students on mathematics learning outcomes at SMK N 1 Sosorgadong included students being able to communicate and socialize effectively with fellow students, education staff, educators, parents and the surrounding community.